2002
DOI: 10.1111/1467-8489.00184
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic varieties and productivity of smallholder cotton farmers in China

Abstract: Genetically modified cotton varieties have greater production efficiency for smallholders in farming communities in China. We also find that the adoption of Bacillus thuringiensis (Bt) cotton varieties leads to a significant decrease in the use of pesticides. Hence, we demonstrate that Bt cotton appears to be an agricultural technology that improves both production efficiency and the environment. In terms of policies, our findings suggest that the government should investigate whether or not they should make a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
121
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 15 publications
10
121
2
4
Order By: Relevance
“…Actually, the damage control model has been widely used in recent decades to study marginal productivity of pesticides in rice, cotton and vegetable production, which all further suggested that pesticides are over-utilized [15][16][17]. For example, Huang et al, in their analysis of rice farming in China, suggested that, on the one hand, pesticides contribute significantly to increase rice production; on the other hand, the marginal contribution of pesticides decline considerably with increasing use of pesticides and approached zero at current average pesticide use level by the rice farmers [15].…”
Section: Measuring Marginal Productivity Of Pesticides and Determininmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the damage control model has been widely used in recent decades to study marginal productivity of pesticides in rice, cotton and vegetable production, which all further suggested that pesticides are over-utilized [15][16][17]. For example, Huang et al, in their analysis of rice farming in China, suggested that, on the one hand, pesticides contribute significantly to increase rice production; on the other hand, the marginal contribution of pesticides decline considerably with increasing use of pesticides and approached zero at current average pesticide use level by the rice farmers [15].…”
Section: Measuring Marginal Productivity Of Pesticides and Determininmentioning
confidence: 99%
“…First, we independently analyze the relationship between inputs and outputs, regardless of the factor of price [16,17]. Second, we include the factor of price and analyze the relationship between cost and revenue [9,36].…”
Section: Regression Model Of Marginal Productivity Of Pesticidementioning
confidence: 99%
“…(Huang et al, 2002a(Huang et al, , 2002b(Huang et al, et 2002c Fok (2006) 3 a également conclu que « les méthodes par lesquelles les résultats sont obtenus et rapportés sont tout aussi discutables ». Il a identifié d'autres hypothèses qui mèneraient à une surestimation des avantages du coton Bt dans les budgets partiels.…”
Section: Principales Limites Des Analysesunclassified
“…Ce biais d'auto-sélection résulte du fait que les facteurs qui influencent le producteur, dans sa décision de ou de ne pas cultiver une plante transgénique, pourraient également affecter les bénéfices réalisés. Gouse et al, 2005 ;Huang et al, 2002a ;Huang et al, 2002b ;Pemsl et al, 2005 ;Qaim, 2003 ;Qaim et Zilberman, 2003 ;. Kuosmanen et al (2006) ont proposé une technique semi-paramétique à deux étapes pour modéliser l'interaction entre la pression des ravageurs et l'utilisation d'intrants pour le contrôle des dommages.…”
Section: Principales Limites Des Analysesunclassified
“…The primary benefit of transgenic cotton over conventional cotton in China has been reduced insecticide use. As a result of greater protection against bollworm damage with transgenic cotton 47-75 percent less kilograms of insecticide, or 4-13 fewer insecticide applications, were needed to control these pests, reductions in insecticide use associated with transgenic cotton have varied regionally, and in regions where bollworms are not the primary cotton pests, farmers growing transgenic cotton observed a decrease in their insecticide use as low as 14 percent (Huang et al, 2002c). Therefore, farmers in regions with few bollworms may not benefit as much from adopting transgenic cotton as farmers in areas where bollworm are key pest.…”
mentioning
confidence: 99%